Parameter PVlim kot merilo za ovrednotenje materialov tesnilnih obročev v mehanskih drsnih tesnilih - Vezjak, Anton (Materiali in tehnologije, 2000)
Seal face evaluation criteria have not been standardized yet, however, the most common approach for seal face evaluation is to determine a performance limit of parameter ?$PV_{lim}$?. Beside physical properties of both seal faces parameter ?$PV_{lim}$? is influenced by lubrication, seal design and operating conditions. The literature contains very little information on the relationship of ?$PV_{lim}$? to this influence factors. In our study the influence of different lubrication regime on the parameter ?$PV_{lim}$? has been investigated. For this purpose we have tested several materials under different tribological loading or different values of parameter PV. The results have shown that certain regime of lubrication which occurs in sealing gap has great influence on values of parameter ?$PV_{lim}$? and therefore on seal life.
Keywords: tesnila; tesnjenje; mazanje; vplivi; tlak; hitrost